2012
DOI: 10.2223/jped.2205
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive predictors of esophageous varices in children and adolescents with chronic liver disease or extrahepatic portal venous obstruction

Abstract: Objective: To identify non-invasive predictors of esophageal varices in children and adolescents with chronic liver disease or extrahepatic portal venous obstruction (EHPVO).Methods: 53 patients younger than 20 years with chronic liver disease or EHPVO and no history of bleeding or prophylactic treatment of esophageal varices (EV) were assessed. They were divided into 2 groups: group I (35 with chronic liver disease) and group II (18 with EHPVO). Their blood count, international normalized ratio (INR), albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…To avoid unnecessary endoscopy, especially in low-risk patients, many studies have been carried out to identify noninvasive factors that may predict the presence of gastroesophageal varices [20e22]. Thus, the number of noninvasive tools for gastroesophageal varices has been growing rapidly over the years, including biochemical, clinical, and ultrasonography parameters [23,24]. However, in our series we did not find difference in variables such as platelet count, spleen measure, and reversal flow in portal vein.…”
Section: Discussioncontrasting
confidence: 63%
“…To avoid unnecessary endoscopy, especially in low-risk patients, many studies have been carried out to identify noninvasive factors that may predict the presence of gastroesophageal varices [20e22]. Thus, the number of noninvasive tools for gastroesophageal varices has been growing rapidly over the years, including biochemical, clinical, and ultrasonography parameters [23,24]. However, in our series we did not find difference in variables such as platelet count, spleen measure, and reversal flow in portal vein.…”
Section: Discussioncontrasting
confidence: 63%
“…We found a strong positive relation between the presence of EV and the reduction of platelets count, with the cutoff point of 117,000.mm³. Alcântara et al [21] in their retrospective study with Brazilian children and adolescents with PH found the platelets cutoffs points of 92,000/mm³ for patients with EV and of 118,000/mm³ for those without EV.…”
Section: Discussionsupporting
confidence: 59%
“… 64 67 Other blood tests that were determined to predict varices were platelet count (sensitivity 56-76%; specificity 64-88%) and AST-to-platelet Index (sensitivity 59-86%; specificity 64-81%). 62 64 68 69 70 Among the doppler ultrasound parameters only hepatic artery resistive index was found to be associated with presence of varices. 55 57 …”
Section: Varicesmentioning
confidence: 96%